Pendidikan Anti-Korupsi - sumiarti sumiarti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Corruption is human mentality problem associated with greed and asocial. Ironically, in the herald of ideal education concept, what that produced was people that more astute and slippery to corrupt. The rise of white-collar crime is a sign of poor education quality that fail to produce moral people. Education that have duty to develop human potential and as a cultural inheritance process have huge share to produce human with good moral, intelligent, and competent, which have vital role to combat corruption. Education in Indonesia has been distorted and tends to give priority to legal-formal aspect. On removing corruption context, education has to produce human that have commitment to values and virtues to become good people, namely explicit to combat corruption.Â